The Actor's book of scenes from new plays - Lane, Eric; Shengold, Nina (Penguin Books, 1988)
David Mamet, Beth Henley, and August Wilson are just some of the contemporary dramatists whose work is featured in this book, the first anthology of two-character scenes that exclusively includes plays from the mid-sixties to plays currently running on and off Broadway.